2017
DOI: 10.1002/bdm.2041
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Opportunity Cost Neglect in the Poor

Abstract: People often neglect opportunity costs: They do not fully take into account forgone alternatives outside of a particular choice set. Several scholars have suggested that poor people should be more likely to spontaneously consider opportunity costs, because budget constraints should lead to an increased focus on trade‐offs. We did not find support for this hypothesis in five high‐powered experiments (total N = 2325). The experiments used different products (both material and experiential) with both high and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…The results show that reminding people of opportunity cost, prior to their donation decision, decreases their willingness to donate. The results for the first decision are in line with the findings from proself spending (Frederick et al, 2009;Plantinga et al, 2018), and also how people react to economic evaluations when asked to donate time (DeVoe and Pfeffer, 2010). However, the opportunity cost effect decreased from 13.7 to 4.4% when participants made sequential donation decisions.…”
Section: Discussion Studysupporting
confidence: 79%
See 2 more Smart Citations
“…The results show that reminding people of opportunity cost, prior to their donation decision, decreases their willingness to donate. The results for the first decision are in line with the findings from proself spending (Frederick et al, 2009;Plantinga et al, 2018), and also how people react to economic evaluations when asked to donate time (DeVoe and Pfeffer, 2010). However, the opportunity cost effect decreased from 13.7 to 4.4% when participants made sequential donation decisions.…”
Section: Discussion Studysupporting
confidence: 79%
“…In these studies, opportunity cost became salient simply by adding the text "save the money for other purchases" next to the not-purchase-option. Previous studies investigating opportunity cost suggest that people primarily attend to explicitly presented options (Jones et al, 1998;Greenberg and Spiller, 2016;Plantinga et al, 2018) and thus, opportunity cost neglect occurs when other options (i.e., alternative use of money) remain implicit (Jones et al, 1998;Frederick et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research has typically found that consumers neglect opportunity costs and tradeoffs (Frederick, Novemsky, Wang, Dhar, & Nowlis, 2009)-that is, consumers rarely think about what they are giving up when they make a purchasethis may be less true for consumers who are financially constrained. There is some evidence that opportunity costs may be more psychologically salient for consumers facing scarcity (Shah et al, 2015;Spiller, 2011), though other evidence suggests that low and high income consumers are equally likely to spontaneously consider opportunity costs (Plantigna, Krijnen, Zeelenberg, & Bruegelmans, 2018). For example, in one study, participants completed a hypothetical shopping task.…”
Section: Stress and Anxiety Feeling Lack Of Controlmentioning
confidence: 99%
“…This measure was used in the Biannual European Social Survey (http://www.europeansocialsurvey.org/). Support of validity for this measure is shown by its relationship with family income (Plantinga, Krijnen, Zeelenberg, & Breugelmans, 2018).…”
Section: Methodsmentioning
confidence: 90%